Low pressure direct injection strategies effect on a small SI natural gas two-stroke engine's energy distribution and emissions. (15th November 2018) - Darzi, Mahdi; Johnson, Derek; Ulishney, Chris; Clark, Nigel
Highlights: LPDI increased indicated efficiency to 28–30% dependent on engine speed. Start of direct injection at 180 CA BTDC minimized fuel loss. LPDI met current emissions regulations, cutting fuel slip by over a factor of 2. Higher volumetric efficiency led to increased power density. LPDI augmented energy distribution, to capitalize on heat recovery for CHP. Abstract: This paper examines methods to simultaneously improve efficiency and reduce emissions from a 34 cc air-cooled two-stroke engine configured to operate on natural gas, using tuned intake plus exhaust resonators designed from Helmholtz resonance theory to promote effective scavenging. The engine was developed for novel application in a small, free piston engine for decentralized power generation. Operation occurred at wide-open-throttle at a speed of 5400 RPM for both port injection (PI) and low-pressure direct injection (LPDI). In both cases, the electronic ignition timing was adjusted for maximum brake torque, while the fuel was adjusted such that both rich and lean combustion were examined. The LPDI engine was then operated over a variety of engine speeds. An energy balance was completed for both PI and LPDI operation, which quantified all energy pathways, as engine operating regimes changed. Results showed that exhaust chemical energy (ECE) for LPDI was reduced significantly when compared to PI, mostly due to less fuel slip. The fuel slip rate ranged from 35 to 40% for PI operation while it was in the range of 6–20% for LPDI operation. However, mixture stratification with LPDI operation increased carbon monoxide emissions. The start-of-injection (SOI) was also examined, targeting a SOI to provide the highest trapping efficiency and most stable combustion. For LPDI operation, trapping efficiency, which is function of engine speed, showed significant effects on overall efficiency and fuel slip. Air volumetric efficiency increased due to the absence of gaseous fuel within the intake manifold. It was shown that, relative to PI, the overall engine indicated efficiency increased by 90% to a maximum indicated efficiency of 30% for LPDI operation with a SOI of 180 CAD BTDC.